Gut Microbiota Dynamics in Obesity and Metabolic Regulation - Abeer Hadi Farhood; Semaa Hassen Shalal (Academia Open, 2025)
General Background: Obesity is one of the fastest-growing global public health challenges, contributing to over 60% of deaths linked to elevated body mass index (BMI). Specific Background: Emerging evidence highlights the gut microbiota as a critical factor in the onset and progression of obesity by influencing dietary energy extraction and regulating host genes involved in fat storage and metabolism. Knowledge Gap: While the relationship between gut microbiota and metabolic health is increasingly recognized, the mechanisms through which microbial modulation can be translated into effective preventive or therapeutic strategies remain insufficiently explored. Aim: This study emphasizes the role of gut microbiota in health and disease, with a focus on the potential of probiotics and prebiotics to improve gut and immune health. Results: Findings demonstrate that gut microbiota composition is highly variable and shaped by diet, nutrients, lifestyle, and environmental exposures, suggesting its potential as a modifiable factor in obesity prevention. Novelty: This review underscores the dynamic nature of gut microbiota and positions its modulation through dietary and microbial interventions as a promising strategy for obesity management. Implications: Promoting microbial balance with prebiotics, probiotics, fermented foods, fruits, and vegetables, while reducing intake of saturated fats and refined sugars, offers a feasible and evidence-based approach for the prevention and treatment of obesity. Highlights: Gut microbiota influences energy balance and fat storage, impacting obesity development  Probiotics and prebiotics can help restore microbial balance for obesity prevention  Dietary patterns and lifestyle strongly shape gut microbial composition and diversity Keywords: Gut Microbiota, Obesity, Prevention, Dietary Strategies